2002
DOI: 10.1677/joe.0.1720155
|View full text |Cite
|
Sign up to set email alerts
|

The HIV protease inhibitor saquinavir impairs lipid metabolism and glucose transport in cultured adipocytes

Abstract: Treatment of HIV infection using protease inhibitors is frequently associated with lipodystrophy and impaired lipid and glucose metabolism. We examined the effect of saquinavir, one of the protease inhibitors, on lipid metabolism and glucose transport in cultured adipocytes. Saquinavir inhibited lipoprotein lipase (LPL) activity in 3T3-F442A and 3T3-L1 adipocytes. The inhibition of LPL was 81% at a concentration of 20 µg/ml. Another closely related drug, indinavir, had a small inhibitory effect. Saquinavir als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 34 publications
7
35
1
1
Order By: Relevance
“…Because this occurred in the face of increased plasma insulin levels, these observations provide evidence for impaired suppression of lipolysis by insulin. The latter is consistent with recent reports that nelfinavir, saquinavir, and ritonavir increase lipolysis (11,35,37). We found no alteration of plasma lipids except for an increase in LDL cholesterol.…”
Section: Discussionsupporting
confidence: 93%
“…Because this occurred in the face of increased plasma insulin levels, these observations provide evidence for impaired suppression of lipolysis by insulin. The latter is consistent with recent reports that nelfinavir, saquinavir, and ritonavir increase lipolysis (11,35,37). We found no alteration of plasma lipids except for an increase in LDL cholesterol.…”
Section: Discussionsupporting
confidence: 93%
“…These results on lipolysis did not agree with those reported by others (8,19,20). The differences, however, could have been due to the use of a different PI (i.e., Nelfinavir) in the studies cited (8,19,20) and the PI concentrations employed (maximum concentrations used in other studies (8,(22)(23)(24) (Ͼ20.0 M). Also, our protocol had PI present during fat cell differentiation while others did not expose the adipocytes until differentiation was complete, upon which the PI was added for 18 h-48 h before measuring lipolysis (8).…”
Section: Discussioncontrasting
confidence: 55%
“…These included the 3T3 L1 pre-adipocytes (this study), 3T3 F442A pre-adipocytes (19), and C3H10T1/2 cells (8) Further, the concentrations of PI used in this study are in the physiological range (3)(4)(5). The clinical evidence on insulin resistance and adiposity indicated that multiple sites are affected in fat tissue (23,24). Our data indicate that the effects of PI while elevating basal TG synthesis are not manifested by increased insulin-stimulated TG synthesis.…”
Section: Discussionmentioning
confidence: 95%
“…The 3T3-L1 adipocyte, however, did not exhibit increased insulin-stimulated 2-DG transport after short-term exposure to PI and showed decreased basal 2-DG transport (Murata et al 2000). Controversy does exist as others (Ranganathan & Kern 2002) have shown increased basal 2-DG transport in 3T3-L1 adipocytes in the presence of indinavir and saquinavir. Also, they showed little or no effect of PI on insulin-stimulated 2-DG transport.…”
Section: Discussionmentioning
confidence: 91%